Schottky forward current transport mechanisms in AlGaN/GaN HEMTs over a wide temperature range - 武玫 郑大勇 王媛 陈伟伟 张凯 马晓华 张进成 郝跃 (Chinese physics B, 2014)
The behavior of Schottky contacts in AlGaN/GaN high electron mobility transistors （HEMTs） is investigated by temperature-dependent current-voltage （T-I-V） measurements from 300 K to 473 K. The ideality factor and barrier height determined based on the thermionic emission （TE） theory are found to be strong functions of temperature, while present a great deviation from the theoretical value, which can be expounded by the barrier height inhomogeneities. In order to determine the forward current transport mechanisms, the experimental data are analyzed using numerical fitting method, considering the temperature-dependent series resistance. It is observed that the current flow at room temperature can be attributed to the tunneling mechanism, while thermionic emission current gains a growing proportion with an increase in temperature. Finally, the effective barrier height is derived based on the extracted thermionic emission component, and an evaluation of the density of dislocations is made from the I-V characteristics, giving a value of 1.49 × 10^7 cm^-2.